On the Intergenerational Incidence of Wage and Consumption Taxes - Berthold U. Wigger (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper analyzes the intergenerational incidence of wage and consumption taxes imposed to finance a given amount of public expenditures. It employs a continuous time overlapping genera-tions framework to demonstrate that it essentially hinges on the relationship between the age-earnings and age-consumption profiles of the households which generations bear the major burden of wage respectively consumption taxes. Furthermore, the paper points to some political economy implications of the incidence of wage and consumption taxes.
Keywords: 330; Intergenerational incidence; wage and consumption taxes; life cycle model